Harnessing the Gut-Brain Axis for Pain Management in Sport: A Review of Microbiome-Targeted Interventions - Korzeniowska, Anna; Stołecka, Greta; Kolasa, Wiktoria; Szeliga, Katarzyna; Kolanko, Magdalena; Grabowska, Julia; Kosidło, Patrycja; Jędrysiak, Joanna; Mikółka, Karolina; Lelonkiewicz, Martyna (Quality in Sport, 2026)
Background. Pain affects approximately 20% of adults worldwide, representing a significant global health challenge and a frequent reason for primary care visits. In the context of sports and physical activity, effective pain management is a cornerstone of maintaining athlete well-being and optimizing long-term performance. Recent evidence suggests that the gut-brain axis serves as a critical bidirectional communication system influencing pain through various pathways. Aim This review aims to examine the mechanisms by which the gut microbiome modulates pain perception and to explore the therapeutic potential of microbiome-targeted interventions in clinical practice. Material and methods. A systematic review of literature from PubMed, Web of Science, and Scopus was conducted up to early 2026. The search focused on high-impact research regarding the gut-brain axis, neuroinflammation, and microbial metabolites, specifically in conditions such as Irritable Bowel Syndrome (IBS), migraine, and fibromyalgia. Results. The gut microbiome influences pain via the production of short-chain fatty acids (SCFAs), neurotransmitters like serotonin and GABA, and the maintenance of intestinal barrier integrity. Dysbiosis can lead to a "leaky gut," allowing pro-inflammatory mediators like lipopolysaccharide (LPS) to sensitize nociceptive neurons. Clinical data show that low-FODMAP diets and water-soluble fibers are effective for IBS pain. Probiotics and fecal microbiota transplantation (FMT) show promise in managing pain for migraine and fibromyalgia patients. Conclusions. The gut microbiome is a key modulator of pain perception. While microbiome-targeted therapies like probiotics and FMT show therapeutic potential, effects are often strain-specific. Future research should utilize large-scale multi-omic studies to develop precision treatments for chronic pain disorders.